Bidirectional two-sample Mendelian randomization analysis identifies causal associations between migraine and five psychiatric disorders - Li, Wen-Wei; Zhang, Jia-Xin; Wang, Jia; Chen, Ya-qing; Lai, Sha; Qiu, Zhi-Kun (Frontiers in Neurology, 2024)
Background The question of whether a correlation exists between migraine and five psychiatric disorders, including posttraumatic stress disorder (PTSD), major depressive disorder (MDD), anorexia nervosa (AN), bipolar disorder (BIP), and schizophrenia (SCZ), remains a matter of controversy. Hence, this research aims to investigate whether there is a possible association between migraine and five psychiatric disorders. Methods We performed a bidirectional 2-sample Mendelian randomization (MR) analysis to assess the causality between migraine and five psychiatric disorders. Genetic associations of PTSD, MDD, AN, BIP, and SCZ were obtained from the Psychiatric Genomics Consortium (PGC) database and genetic associations of migraine with aura and migraine without aura were obtained from the FinnGen dataset. We used the inverse-variance weighted (IVW), weighted median, weighted mode, MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO), and MR Egger regression methods to evaluate the association of genetically predicted exposure with the risk of outcome. Results MR demonstrated that MDD was associated with a high risk of migraine without aura (OR = 1.930578, 95% confidence interview (CI): 1.224510, 3.043550, p < 0.05), but BIP was related to a low risk of migraine without aura (OR = 0.758650, 95%CI: 0.639601, 0.899858, p < 0.05). According to the results of reverse MR, migraine with aura was associated with a high risk of BIP (OR = 1.019100, 95%CI: 1.002538, 1.035935, p < 0.05), and migraine without aura was associated with an increased risk of AN (OR = 1.055634, 95%CI: 1.023859, 1.088394, p < 0.05). Conclusion Our results provide evidence of the potential causal association between migraine and some psychiatric disorders. It may contribute to the prevention of migraine and some psychiatric disorders.